2012
DOI: 10.1080/10934529.2012.687248
|View full text |Cite
|
Sign up to set email alerts
|

In vitroandIn vivoantimicrobial activity of propolis on the microbiota from gastrointestinal tract of chickens

Abstract: The aim of this study was to examine the effect of propolis extracts on the microbial colonization of chicken gastrointestinal tract in vivo. The propolis was administered to both feed mixtures in various amounts except of the control group. The addition of 150 mg propolis to 1 kg of feed was included in the first experimental group, the addition of 450 mg.kg(-1) in the second experimental group, the addition of 600 mg.kg(-1) the third experimental group and 800 mg kg(-1) in the fourth one. The highest count o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
19
1
3

Year Published

2013
2013
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 29 publications
(27 citation statements)
references
References 28 publications
4
19
1
3
Order By: Relevance
“…Similarly, Kačániová et al. () showed a lower number of Enterobacteriaceae genera in chickens fed with 800 ppm of EEP. Enterobacteriacea inhibition in human faecal samples by some active compounds of propolis, such as caffeic acid, has been shown (Lee et al., ).…”
Section: Discussionmentioning
confidence: 80%
See 3 more Smart Citations
“…Similarly, Kačániová et al. () showed a lower number of Enterobacteriaceae genera in chickens fed with 800 ppm of EEP. Enterobacteriacea inhibition in human faecal samples by some active compounds of propolis, such as caffeic acid, has been shown (Lee et al., ).…”
Section: Discussionmentioning
confidence: 80%
“…On the other hand, Kačániová et al. () did not show any changes of lactobacilli number in the gastrointestinal tract of chicken fed EEP. The controversial results regarding the effect of propolis on lactic acid bacteria may be correlated with differences in propolis composition.…”
Section: Discussionmentioning
confidence: 90%
See 2 more Smart Citations
“…As Kačániová et al (2012) reported that feeding of propolis to chickens increased enterococcus and lactobacillus in excreta, propolis residue seems to have the potency to increase the growth of some kinds of bacteria. Boyanova et al (2006) reported that Bulgarian propolis was highly active against the anaerobic bacteria including Prevotellaceae.…”
Section: Discussionmentioning
confidence: 88%